2016
DOI: 10.1021/jacs.6b03187
|View full text |Cite
|
Sign up to set email alerts
|

Solar-Driven Water Oxidation and Decoupled Hydrogen Production Mediated by an Electron-Coupled-Proton Buffer

Abstract: Solar-to-hydrogen photoelectrochemical cells (PECs) have been proposed as a means of converting sunlight into H2 fuel. However, in traditional PECs, the oxygen evolution reaction and the hydrogen evolution reaction are coupled, and so the rate of both of these is limited by the photocurrents that can be generated from the solar flux. This in turn leads to slow rates of gas evolution that favor crossover of H2 into the O2 stream and vice versa, even through ostensibly impermeable membranes such as Nafion. Herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 49 publications
1
103
1
Order By: Relevance
“…H 6 SiW V 2 W VI 10 O 40 released protons to effectively generate highly pure H 2 (only 0.08 % O 2 ) on a Pt/C surface . A WO 3 ‐FTO photoanode in 1 M CH 3 SO 3 H (pH 1) under visible light generated electricity as well as oxygen, whereas H 3 PMo 12 O 40 was reduced in conjunction with proton coupling to H 5 PMo 12 O 40 on carbon felt as a cathode in water at pH 0.1 . When H 5 PMo 12 O 40 was reoxidized to H 3 PMo 12 O 40 , H 2 was evolved in a 100 % Faradaic yield, implying that this system should be an excellent H 2 storage method.…”
Section: Next‐generation Energy With Poms: Fuel Cells Water Splittinmentioning
confidence: 99%
“…H 6 SiW V 2 W VI 10 O 40 released protons to effectively generate highly pure H 2 (only 0.08 % O 2 ) on a Pt/C surface . A WO 3 ‐FTO photoanode in 1 M CH 3 SO 3 H (pH 1) under visible light generated electricity as well as oxygen, whereas H 3 PMo 12 O 40 was reduced in conjunction with proton coupling to H 5 PMo 12 O 40 on carbon felt as a cathode in water at pH 0.1 . When H 5 PMo 12 O 40 was reoxidized to H 3 PMo 12 O 40 , H 2 was evolved in a 100 % Faradaic yield, implying that this system should be an excellent H 2 storage method.…”
Section: Next‐generation Energy With Poms: Fuel Cells Water Splittinmentioning
confidence: 99%
“…Previously, we introduced the electron‐coupled‐proton‐buffer (ECPB) to separate the process of water splitting in time and space . In this way, the hydrogen evolution reaction (HER) is no longer coupled with the rate‐limiting step of the oxygen evolution reaction (OER).…”
Section: Figurementioning
confidence: 99%
“…Therefore, decoupled water splitting represents an excellent strategy in avoiding this H 2 /O 2 mixing issue for solar‐driven water electrolysis. Following their success in utilizing phosphomolybdic acid as the ECPB for electrochemical decoupled water splitting, the Cronin group further demonstrated that this strategy could be applied in solar‐driven water splitting as well . As shown in Figure a, WO 3 was adopted as an effective photoanode due to its suitable band gap which straddles both O 2 evolution onset (1.2 V vs NHE) and the reduction potential of [PMo 12 O 40 ] 3− (∼0.6 V vs NHE), as well as great stability under strongly acidic condition.…”
Section: Decoupled Water Splitting In Acidic Electrolytementioning
confidence: 99%